BALANCE, SPEED, AND EXPLOSIVE STRENGTH OF LEGS OF BASKETBALL PLAYERS AS A FUNCTION OF HIGH INTENSITY PLYOMETRIC EXERCISES AND PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION EXERCISES - Kanetkar, Saket D.; Tiwari, Surendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Basketball players require a unique combination of physical attributes, including explosive power, speed, balance, and coordination, to excel in the sport. High-intensity plyometric exercises and proprioceptive neuromuscular facilitation (PNF) exercises are two highly effective training modalities that can help players develop these critical qualities. Hence, the study of balance, speed, and explosive leg strength in basketball players is essential for optimizing performance, preventing injuries, and fostering long-term athletic development. These attributes are fundamental to the physical demands of basketball and directly influence a player’s ability to succeed on the court. By focusing on these areas, coaches, trainers, and athletes can gain a competitive edge, improve overall fitness, and ensure sustained success in the sport. In view of the above this study was conducted to assess the impact of High-intensity plyometric exercises and proprioceptive neuromuscular facilitation (PNF) exercises on select physical fitness variables of basketball players of Nagpur District. All the necessary data was collected through experimental procedures and was critically analysed using SPSS 18.0 statistical software. The study results showed that that better balance and speed can be achieved through HI Plyometric exercise.